PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII UPTD SMP NEGERI 5 KUPANG TENTANG SISTEM PEREDARAN DARAH - Fajriani Kirutang; Mbing Maria Imakulata; Andam S. Ardan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This research was conducted on May 22 and May 27, 2025, at UPTD SMP Negeri 5 Kupang. The study aimed to determine the impact of implementing the Problem-Based Learning (PBL) model on the learning outcomes of Grade VIII students at UPTD SMP Negeri 5 Kupang regarding the circulatory system. The research employed the Classroom Action Research (CAR) method developed by Kemmis and McTaggart, carried out in cycles comprising four stages: planning, acting, observing, and reflecting. The subjects of the study were 30 Grade VIII students. Data collection techniques included observations of teachers and students, evaluation test results, and documentation. The results indicated an improvement in student learning outcomes regarding the circulatory system topic. Observations of student activity showed a rise from a 69.64% score (rated